Implementasi Kebijakan Retribusi Pasar Bersehati Kecamatan Wenang Kota Manado. - Tilolango, Indra; Tampi, Gustaaf Budi; Kolondam, Helly (Sam Ratulangi University, 2017)
Abstract: this research aims to know the implementation of the policyof retributionMarket Bersehati Subdistrict Detention Manado city. Thisstudy uses qualitative methods with selected informants consisted of Director of PD. The market townof Manado, head of Retribution PD. Manado City Market, Bersehati Market,Officer Coordinator/Billers Levy Bersehati Market, and Traders in the market Bersehati. Datacollection techniques used are interviews, observation and documentation. Qualitative datawereanalyzed with descriptive narrative supported by primary and secondary data.The results showed thatthe implementation of policies related Market levy Bersehati sub-district of Manado City Detention hasshown a fairly good results, in terms ofattitude, and the compliance officer in carrying out the policy. Thiscan be seen on the Apparatus involved in the implementation of the Bersehati sub-districtof Markets ballot levy arbitrary arrest city that transparency in carrying out the tasks and always refers tothe existing regulations. In addition the adequacy of manpower is already implementing a policy that is goodwith officers and employees of the PD marketManado city that exists in the market Bersehati. Similarly, thedecisions taken in case of problems or constraints in implementation is always good for the commongoodparty PD. Manado City Market or user community market. However for the benefit of employees andresponse against complaint merchants still showed a less good results. Similarly, the strategies used are alljust communication and sosialisai without any action even though the degree of change that's been good tobe achieved, namely repair and upgrading of infrastructure and quality of service. So consequently thetraders became feel aggrieved.Keywords: Implementation Of Policy, Market Levy